Frizzy [book club bag] - Ortega, Claribel A. (First Second, 2022)
Dominican Marlene loves books, her best friend Camila, and her aunt Ruby. She does NOT love having to go to the salon every Sunday to have her curly hair straightened. But her mother tells her it's the only way to look presentable to others. When a bad blowout results in disparaging comments from family members at a party, Marlene embarks on a journey to do something different with her hair. A momentous visit with her aunt Ruby, who wears her hair naturally, helps Marlene embrace her natural curls and confront the toxic ideas about beauty that have been passed down to her.